KALIMAT TANYA DALAM BAHASA DAYAK KANAYATN - Dela Safitri; Hotma Simanjuntak; Agus Syahrani (Universitas Tanjungpura, 2020)
AbstractThe research of interrogative sentence in Dayak Kanayatn Language is a syntaxis study conducted at Bolat Village, Sampuro, Mempawah Hulu District of Landak Regency. The discussion in this study was delimited into three subdivisions, namely features, syntaxis structures, and the form of text negotiating text supplement in DKL. This study aimed to determine the characteristics, syntaxis structures, and the negotiating text supplement in DKL. The method used in this study was descriptive with the form of qualitative research. The data was collected using cakap semuka, recording, and notetaking techniques. The data collection instrument used were interview guidelines, recorders, and notes. According to the research, there were six features of interrogative sentences in DKL: an interrogative sentence with a question mark, an interrogative sentence based on sentence focus and question mark, an interrogative sentence without question mark, alternative interrogative sentence, negative interrogative sentence, and embroidered question sentence. There are fourteen interrogative sentence structures with question marks, four based on sentence focus and question marks, fifteen structures without question marks, eleven structures of an alternative interrogative sentence, ten structures of a negative interrogative sentence, and five structures of an embroidered interrogative sentence.Keywords: Features, Structures, Interrogative Sentences, Dayak Kanayatn